Responsibilities of Parents to Children After Divorce According to Presidential Instruction Number 1 of 1991 Perspective of the Compilation of Islamic Law (JURNAL HUKUM SEHASEN, 2021)
Compilation of Islamic Law, in reality, often an unhappy family or household life occurs. The condition of the marriage is so bad, that from any point of view, it is better to break the marital relationship than to continue it. This means that although marriage is a "very strong agreement (Mitsaqon Ghaliidhan)" that binds physically and mentally between husband and wife, the marriage bond can be broken if husband and wife decide it, because both parties have the right to break the agreement. This is the focus of the author's research, namely the responsibility of parents to children after divorce according to Presidential Instruction No. 1 of 1991 from the perspective of KHI. What are the inhibiting factors for parents who do not carry out their obligations to children after divorce. The method used in this study uses a qualitative descriptive method. Based on the results of the study, the authors conclude that the responsibility of parents to children after divorce in Presidential Instruction Number 1 of 1971 concerning the perspective of compiling Islamic law is still contrary to the law. There are still many parents who have not met the needs and support for their children due to several inhibiting factors. The inhibiting factors are a) Lack of good communication from both parents after a divorce, b) Weak economy, c) Lack of religious knowledge in the family, and d) Distance between children's homes and parents after divorce and especially economic factors which are the core parent problems.